2023
DOI: 10.3390/soilsystems7020047
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Salinity/Sodicity and Salt-Affected Soil Classes from Soluble Salt Ions Using Machine Learning Algorithms

Abstract: Salt-affected soils are related to salinity (high content of soluble salts) and/or sodicity (excess of sodium), which are major leading causes of agricultural land degradation. This study aimed to evaluate the performances of three machine learning (ML) algorithms in predicting the soil exchangeable sodium percentage (ESP), electrical conductivity (ECe), and salt-affected soil classes, from soluble salt ions. The assessed ML models were Partial Least-Squares (PLS), Support Vector Machines (SVM), and Random For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The results of the study indicated that the RF model outperformed the MLR model in terms of accuracy when applied to both the training and validation datasets, consistent with Wang et al [57] This can be attributed to the effectiveness of soluble major ions complex as a predictor for soil salinity. Additionally, the performance of the MLR model was found to be more suitable in cases of multicollinearity, which was observed due to the high correlation among soluble salt ions [58]. However, both two models performed normal when predicting the soil ESP.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the study indicated that the RF model outperformed the MLR model in terms of accuracy when applied to both the training and validation datasets, consistent with Wang et al [57] This can be attributed to the effectiveness of soluble major ions complex as a predictor for soil salinity. Additionally, the performance of the MLR model was found to be more suitable in cases of multicollinearity, which was observed due to the high correlation among soluble salt ions [58]. However, both two models performed normal when predicting the soil ESP.…”
Section: Discussionmentioning
confidence: 94%